7 October 2023 and Its Aftermath Through Edward Said’s Lens - Md. Mahmudul Hasan (Asiatic: IIUM Journal of English Language and Literature, 2025)
The Palestinian tragedy meted out by Israeli settler colonial domination has lasted for many decades. Increasing Israeli atrocities against Palestinians range from targeted killings and settler violence to mass murders, destruction of builtscapes, and denial of basic necessities of life such as food, water, healthcare, and communication systems. After innumerable episodes of calculated unilateral escalation of military violence against Palestinians, Israel has exhibited an increase in its aggressive behaviour in the ongoing genocide in Gaza. Had Edward Said been alive today, he would have taken great interest in interpreting the current events in the region. However, he identified a pattern in Israeli behaviour which has remained unjust to Palestinians since long before the 7 October 2023 event. Israel’s characteristic hostility to Palestinians examined by Said helps us understand its genocidal crimes, which this essay explores.